2021
DOI: 10.3390/medicina57030202
|View full text |Cite
|
Sign up to set email alerts
|

A Typical Case Presentation with Spontaneous Visual Recovery in Patient Diagnosed with Leber Hereditary Optic Neuropathy Due to Rare Point Mutation in MT-ND4 Gene (m.11253T>C) and Literature Review

Abstract: Leber hereditary optic neuropathy (LHON) is one of the most common inherited mitochondrial optic neuropathies, caused by mitochondrial DNA (mtDNA) mutations. Three most common mutations, namely m.11778G>A, m.14484T>G and m.3460G>A, account for the majority of LHON cases. These mutations lead to mitochondrial respiratory chain complex I damage. Typically, LHON presents at the 15–35 years of age with male predominance. LHON is associated with severe, subacute, painless bilateral vision loss and account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…4,5 Besides the undeniable link to the mtDNA alterations, Leber´s Hereditary Optic Neuropathy has proven to be far more complex as a diseaseenvironmental triggers such as excessive smoking and alcohol consumption may start the disease on mutation carriers. 3 Other factor concerns the gender of patientssome studies present data on relation of hormonal diferences between male and female. The higher level of estrogen, for example, may be related to less cases of LHON affecting women, though they may be carriers of gene mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Besides the undeniable link to the mtDNA alterations, Leber´s Hereditary Optic Neuropathy has proven to be far more complex as a diseaseenvironmental triggers such as excessive smoking and alcohol consumption may start the disease on mutation carriers. 3 Other factor concerns the gender of patientssome studies present data on relation of hormonal diferences between male and female. The higher level of estrogen, for example, may be related to less cases of LHON affecting women, though they may be carriers of gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen is also related to exert neuroprotective effect on retinal ganglion cells during heightenned cellular stress, which may explain more severe symptons on men compared to women. 3 There are few studies on Leber´s Hereditary Optic Neuropathy. Most of them are conducted on diferent countries.…”
Section: Discussionmentioning
confidence: 99%
“…Two of those, 13340T>C and 13379A>G, were in MT‐ND5 , while there was one mutation each in MT‐ND6 (14538A>G), MT‐ND3 (10350C>A), and MT‐ND1 (3632C>T) (Peverelli et al, 2021). Some other type of rather rare mutations linked to LHON are 1253T>C in MT‐ND4 (Liutkeviciene et al, 2021), 13345G>A in MT‐ND5 (Engvall et al, 2021), 3890G>A in MT‐ND1 (Vacchiano et al, 2021). Achilli et al reported a case study in which they identified nine rare mutations in MT‐ND1 (3700G>A,3733G>A‐C),4171C>A), MT‐ND4L (10663T> CA), and MT‐ND6 (14459G>A, 14495A>G, 14482C>A, and 14568C>T) (Achilli et al, 2012).…”
Section: Rcs Alterations and Mitochondrial Diseasesmentioning
confidence: 99%